2020
DOI: 10.1038/s41419-020-03236-9
|View full text |Cite
|
Sign up to set email alerts
|

LINC01106 post-transcriptionally regulates ELK3 and HOXD8 to promote bladder cancer progression

Abstract: Bladder cancer (BCa) is a kind of common urogenital malignancy worldwide. Emerging evidence indicated that long noncoding RNAs (lncRNAs) play critical roles in the progression of BCa. In this study, we discovered a novel lncRNA LINC01116 whose expression increased with stages in BCa patients and closely related to the survival rate of BCa patients. However, the molecular mechanism dictating the role of LINC01116 in BCa has not been well elucidated so far. In our study, we detected that the expression of LINC01… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 37 publications
0
23
0
Order By: Relevance
“…Among the seven GInlncRNAs, LINC01133, LINC01671, LINC01116, FAM83A-AS1, and PLAC4 were risk factors for survival, whereas MIR223HG and AL590226.1 were protective factors for patient prognosis. Of note, LINC01133 ( Zhang et al, 2015 ; Zhai et al, 2020 ; Li et al, 2020 ; Liu and Xi, 2020 ; Yang W. et al, 2020 ), LINC01116 ( Cui et al, 2020 ; Meng et al, 2020 ), and FAM83A-AS1 ( He and Yu, 2019 ; Shi et al, 2019 ; Huang et al, 2020 ) have already been identified to be involved in tumorigenesis and malignant progression in lung cancer or other tumors. For example, Zang et al (2016) reported that the upregulated expression of LINC01133 in NSCLC was associated with poor patient survival.…”
Section: Discussionmentioning
confidence: 99%
“…Among the seven GInlncRNAs, LINC01133, LINC01671, LINC01116, FAM83A-AS1, and PLAC4 were risk factors for survival, whereas MIR223HG and AL590226.1 were protective factors for patient prognosis. Of note, LINC01133 ( Zhang et al, 2015 ; Zhai et al, 2020 ; Li et al, 2020 ; Liu and Xi, 2020 ; Yang W. et al, 2020 ), LINC01116 ( Cui et al, 2020 ; Meng et al, 2020 ), and FAM83A-AS1 ( He and Yu, 2019 ; Shi et al, 2019 ; Huang et al, 2020 ) have already been identified to be involved in tumorigenesis and malignant progression in lung cancer or other tumors. For example, Zang et al (2016) reported that the upregulated expression of LINC01133 in NSCLC was associated with poor patient survival.…”
Section: Discussionmentioning
confidence: 99%
“…HOX proteins encoded by HOX genes are key components of substantial metabolic processes such as lipidic metabolism, and their [brain cancer mainly includes the glioma and neuroblastoma (4)(5)(6)(7)(8)(9)(10)(11), lung cancer (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24), hepatocellular carcinoma (25)(26)(27)(28)(29)(30)(31), bladder cancer (32,33), cholangiocarcinoma (34), head and neck squamous cell carcinoma (35,36), breast cancer (21)(22)(23)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)…”
Section: Physiological Function Of Hox Genesmentioning
confidence: 99%
“…Regulation of HOX factors in various tumor types described in this figure legend. [brain cancer mainly includes the glioma and neuroblastoma (4-11), lung cancer(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24), hepatocellular carcinoma(25)(26)(27)(28)(29)(30)(31), bladder cancer(32,33), cholangiocarcinoma(34), head and neck squamous cell carcinoma(35,36), breast cancer(21-23, 37- 54), gastric carcinoma and esophagus cancer(55)(56)(57)(58)(59)(60)(61)(62)(63)(64), prostate cancer and renal carcinoma(43,(65)(66)(67)(68)(69)(70)(71)(72), ovarian cancer (73-79), endometrial cancer and cervical cancer(80)(81)(82)(83)(84), leukemia<...>…”
mentioning
confidence: 99%
“…LINC01116 increases the expression of ELK3 by adsorbing miR-3612 and stabilizes HOXD8 mRNA by binding with DKC1. With the combination of ELK3 and HOXD8, LINC01116 promotes cell proliferation, metastasis, and the EMT process [ 147 ].…”
Section: Emt Processmentioning
confidence: 99%